OP0097 Juvenile idiopathic arthritis (JIA) is associated with the D6S265 microsatellite polymorphisms on the high-risk DR8-DQ4 haplotype. (1st June 2001) - Smerdel, A; Lie, BA; Ploski, R; Undlien, DE; Flato, B; Thorsby, E; Forre, O
Abstract : Background: Juvenile idiopathic arthritis (JIA) has been shown to be associated with at least four different alleles: HLA-A2, DR5 and DR6, and DP2. These associations are independent from each other, i.e. they are not caused by linkage disequilibrium between the markers. However, several studies have suggested that additional, unmapped, HLA-linked genes may participate in JIA. Objectives: The purpose of this study was to look for additional genes involved in the susceptibility for JIA in the HLA complex using microsatellite polymorphisms. Since it is known that JIA is strongly associated with the DR8-DQ4 haplotype only DR8-DQ4 haplotype was included in the study, in order to exclude associations secondary to this high-risk haplotype. Methods: We investigated 102, DRB1*08 positive, patients with JIA classified according to American Collage of Rheumatology criteria. As controls we selected 270, DRB1*08 positive, healthy individuals. We scanned 12 Mb of DNA covering the HLA complex using the following microsatellite polymorphisms, from centromeric to telomeric: D6S291, DQCar, D6S273, MIB, D6S265, D6S2223 and D6S2239. An EM algorythm was used to estimate haplotypes and only the distributions of microsatellite alleles on DR8-DQ4 haplotypes was compared between patients and controls. Results: The microsatellite locus D6S265, which is located centromeric of HLA-A, showed a strong positive association with the disease for the *130 bp allele (OR = 30, p < 1 –6 ). In order to investigate whether this association could be explained by HLA-A2 the frequency of the HLA-A2 allele on DR8-DQ4-D6S265*130 haplotype was compared among patients and controls. However, the D6S265*130 allele still showed evidence for disease association (OR = 23, pp < 1 –5 ). Conclusion: The observed association of D6S265*130 allele with JIA is not secondary to the association of this allele with the DR8-DQ4-A2 haplotype. It shows that D6S265*130 allele could be a marker for additional predisposing factor involved in JIA, and HLA-A2 cannot explain all associations to the JIA in HLA class I region.